P.074 Management, timing of anticoagulation and outcomes of patients with cerebral venous sinus thrombosis: a single centre chart review. (November 2021) - Mak, G; Chan, N; Perera, K
Abstract : Background: Cerebral venous sinus thrombosis (CVST) accounts for <1% of all strokes. Our objectives were to describe the clinical features and examine the association between timing of anticoagulation therapy and outcomes in CVST patients. Methods: We conducted a retrospective chart review of patients admitted to Hamilton Health Sciences from 2015 – 2020 with imaging confirmed CVST. Results: We included 96 patients, mean age of 47.9 (SD 18.1). The most common clinical presentation was headache (43.8%). Brain trauma was the most common identified risk factor (15.6%), while 27% of individuals had no identified cause. Most patients (57.3%) received anticoagulation within 24hrs of identified CVST, while 26% had a delay (≥48hrs) and 16.7% were not anti-coagulated. The rationale for delaying or not starting anticoagulation included traumatic brain injury (31.8%), neurosurgical procedure (9.1%), presence of venous infarct and/or haemorrhage (27.1%) and unclear rationale (31.8%). At a median of 8 days, more patients without clear indications for delayed or no anticoagulation were disabled (defined by modified Rankin Scale, mRS, score ≥ 2) or dead (mRS 6), compared to those anti-coagulated in 24hrs (87.5% versus 31.8%; RR 2.75; 95% CI 1.74 – 4.35). Conclusions: Unjustified delay in anticoagulation may result in poorer clinical outcomes in CVST patients.